Special Issue: Pathophysiology and Therapeutic Perspectives in DMD: The Well-Defined Role of the Immune System - Andrea Farini (Biomedicines, 2021)
Duchenne muscular dystrophy (DMD) is the most common, lethal, muscle-wasting disease of childhood [...]